Legal Analysis of Delay in Compensation Payment for Community Land for The National Strategic Projects Development - Nurul Aini; Ana Silviana (Alauddin Law Development Journal)
This study discusses the priority development projects of the Government to improve Infrastructure, which is expected to benefit the community. In the process there are problems that arise, including delays in payment of compensation for land acquisition for public interest for development. This research method uses an empirical legal approach, data obtained from field research and library research will be analyzed qualitatively to answer the problems in the payment research, there are 3 factors, namely the absence of an accurate budget estimate, incomplete payment files, and there is land in a forest area. Delays in payment of compensation will have economic and social impacts on the community and of course hinder project development for the community. Therefore, to fulfill a sense of justice, legal certainty is needed in the form of clarity regarding compensation for the community.